EFEKTIVITAS PENERAPAN SISTEM AKUNTANSI BERBASIS ONLINE PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KOTA SERANG - Ibrohim, Ibrohim; Surachman, Surachman (Yayasan Education and Social Center, 2025)
This study aims to evaluate the effectiveness of implementing an online-based accounting system in Small and Medium Enterprises (SMEs) in Serang City. Data was collected through interviews, observations, and documentation from various SME owners who adopted online accounting systems. The results indicate that the implementation of online accounting systems has significantly improved operational efficiency, reduced errors in financial recording, and increased the speed and accuracy of financial reporting. Moreover, it has enhanced the transparency of financial statements, facilitating better access to external funding. SMEs reported greater competitiveness after adopting online accounting, benefiting from improved financial management and better decision-making capabilities. The findings highlight the positive impact of online accounting systems in enhancing SME performance, making it easier to manage finances, reduce administrative burdens, and adapt to market competition. This research suggests that more SMEs in Serang City should consider adopting online accounting systems to strengthen financial management, improve business performance, and access external funding opportunities.